A lightweight, user-controlled system for the home - Baillie, Lynne; Schatz, Raimund (Human Technology, 2006)
This paper explores how we designed, with input from some elderly persons, a multi-agent user-controlled network for the home. The system was designed to support the elderly in living longer at home with minimal support. We describe how our work attempts to tackle issues such as privacy, control of personal space, and enjoyment within the home. As the number of elderly individuals' increases, a certain amount of information gathering or support may be required to assist the elderly in their homes. However, we strongly believe that we should preserve people's privacy in their homes and ensure that any artifact we propose is seen as enjoyable, aesthetically pleasing and, most importantly, not stigmatizing. We describe in this paper how a lightweight setup, using a multimodal mobile robot, a PDA, and an interactive television, can assist the elderly in the home in an enjoyable and unobtrusive way.